2008
DOI: 10.1134/s11490-008-4020-4
|View full text |Cite
|
Sign up to set email alerts
|

High-gain erbium-doped fiber amplifier incorporating a double-pass amplification technique as a preamplifier

Abstract: We present a high-gain erbium-doped fiber amplifier to be utilized as a preamplifier. A double-pass amplification technique is used in the first-stage amplifier together with a tunable bandpass filter. The secondstage amplifier is a counter-pumped configuration and another tunable bandpass filter is utilized to filter out amplified spontaneous emission from the firststage amplifier. This design is able to produce a high gain of 55.6 dB and a noise figure of 6.02 dB at 1530 nm with a signal power of −45 dBm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In optical amplifier application, EDFA has been proven to produce substantial gain in the C-band region, reportedly as high as 55.6 dB using double-pass amplification technique [6]. The combination of EDFA with Raman fiber amplifier (RFA) has also been found to offer good manage- ment of channels variation in C-band by employing gain clamping and pump reuse techniques [7].…”
Section: Introductionmentioning
confidence: 99%
“…In optical amplifier application, EDFA has been proven to produce substantial gain in the C-band region, reportedly as high as 55.6 dB using double-pass amplification technique [6]. The combination of EDFA with Raman fiber amplifier (RFA) has also been found to offer good manage- ment of channels variation in C-band by employing gain clamping and pump reuse techniques [7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a single-pass amplifier, the double-pass has higher amplification efficiency, is more cost effective and is more flexible. In the small signal regime, considered in our work, experimental results in the existing literature have shown that the double-pass amplifier is clearly superior to the single-pass amplifier (see also [14], [15]). We use the rate equations derived in Desurvire's paper [18] to study the dynamic amplification for the double-pass configuration.…”
Section: Theoretical Analysis Of Double-pass Fiber Optical Preammentioning
confidence: 65%
“…Previous papers (cf. [11]- [15]) study the amplification properties of the double-pass EDFA, but they do not provide a system performance evaluation. The experimental investigation presented in this paper has been made possible by the recent availability of the polarization-maintaining (PM) fiber Bragg grating (FBG) and the PM circulator.…”
Section: Introductionmentioning
confidence: 99%
“…These are single pass EDFA [24][25][26], double pass EDFA [27][28][29][30][31], many pass EDFA configurations [32][33][34], artificial intelligence applications [35][36][37][38], and temperature characterization [39][40][41][42][43]. In addition, some studies are related to both gain improvement and noise figure in double pass EDFA [44][45][46][47][48][49][50][51][52] proposed an efficient and low noise double-pass L-Band EDFA in their studies [59][60][61].…”
Section: Introductionmentioning
confidence: 99%